If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 9 + 5y + -6 = 4y + 7 + 3y + -2 Reorder the terms: 9 + -6 + 4y + 5y = 4y + 7 + 3y + -2 Combine like terms: 9 + -6 = 3 3 + 4y + 5y = 4y + 7 + 3y + -2 Combine like terms: 4y + 5y = 9y 3 + 9y = 4y + 7 + 3y + -2 Reorder the terms: 3 + 9y = 7 + -2 + 4y + 3y Combine like terms: 7 + -2 = 5 3 + 9y = 5 + 4y + 3y Combine like terms: 4y + 3y = 7y 3 + 9y = 5 + 7y Solving 3 + 9y = 5 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 3 + 9y + -7y = 5 + 7y + -7y Combine like terms: 9y + -7y = 2y 3 + 2y = 5 + 7y + -7y Combine like terms: 7y + -7y = 0 3 + 2y = 5 + 0 3 + 2y = 5 Add '-3' to each side of the equation. 3 + -3 + 2y = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 5 + -3 2y = 5 + -3 Combine like terms: 5 + -3 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| r/8+41=43 | | 6(j+35)=-78 | | 51w+21w-67w=55 | | 5m--30=95 | | 4(x+7)=3(x-8)+x | | 2f-2=2+2f | | 5(x-2)+x=6(x-2)+2 | | b/9--70=76 | | -3z-6=3 | | 50.00+375x=400.00 | | 5(x+9)+7=5x+9 | | .26-.02(x+2)=-.03(1+x) | | 12-2f=8(f+4) | | -3x-3-4x+5=10x-2-7 | | -(w+2)=1 | | y=1/2(4^3) | | x^2+15x+9=0 | | k-10=-2 | | 7=h/2--4 | | 4x-3y=55 | | -2h-5h--14h--14=-14 | | -2(4+6m)+16=-90 | | d^2+10d+18=0 | | v=1/3(6^2)(4) | | 3/10(4x-7)=-3/5x | | t+8/4=3 | | 2w^2-8w-6-w^2+2w-1=0 | | -4t--8=-20 | | 8(x+4)-4=35-6x-7+14x | | X^4-x^2-6x-9= | | x=200+0.8x | | s/4-2=2 |